Penerapan Nilai Akhlak Pergaulan Sesama Siswa melalui Mata Pelajaran PAI dan Budi Pekerti Fase D - Saepul Rohim; Delia Nur Azizah (STAI Al-Musaddadiyah Garut, 2026)
Education is the process of changing a person's behavior and ethics towards a better life and direction, while morals are a reflection of one's soul. The cultivation of morals is very important, considering the reality of many students who violate school, religious and state rules. The purpose of this study is to describe the application of Islamic religious education values ​​​​about social morals among students, through the subject of Islamic Religious Education and Character Building phase D. The method used in this study is a descriptive research method using a qualitative approach. The data sources used are primary data sources (Interviews, observations, and documentation) and secondary data sources (Books and journals that add to the primary data), while the data analysis technique goes through four stages, namely data collection, data reduction, data presentation and drawing conclusions. The results of the study show that the application of Islamic religious education values ​​regarding the morals of social interaction among students, through the subjects of Islamic religious education and character education phase D, in the program of implementing Islamic religious education values ​​including morning dhikr, dhuha prayer, Monday-Thursday fasting, dzuhur and ashar prayers in congregation, etc., in the process of implementing Islamic religious education values ​​runs well and smoothly, and for the morals of social interaction among students in phase D it can be said to be quite good. Keywords: Interaction with Fellow Students, Implementation of Moral Values